Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide

Green chemistry approach to styrene from ethylbenzene and air on MnxTi1-xO2 catalyst - Negi, Sanjay Singh; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy; Singh, Anand Pal; Gopinath, Chinnakonda S. (RSC Advances, 2014)
Styrene (ST) is an industrially important commodity chemical, and design of a suitable catalyst, which provides high ethyl benzene (EB) conversion and styrene selectivity at Lower temperature with sustainable activity, is one of the major challenges in the field of heterogeneous catalysis. Manganese incorporated in titania (MnxT1-xO2) anatase Lattice, prepared via the solution combustion method, was evaluated for oxidative dehydrogenation (ODH) of EB with O-2 or air. MnxTi1-xO2 catalysts were characterized by different physiochemical methods. Up to 15% Mn could be introduced into the TiO2 Lattice. TEM and XRD indicate disordered mesoporosity, further confirmed by adsorption isotherm analysis. MnxTi1-xO2 catalysts were evaluated for ST synthesis from EB using air or oxygen as oxidant between 440 and 570 degrees C. Reaction conditions have been varied systematically, such as catalyst composition, and EB/air/O-2 flow. MnxTi1-xO2 shows sustainable 55% styrene yield for 45 h without deactivation under optimum conditions. A thorough analysis of spent catalysts demonstrates the conversion of initial anatase phase MnxTi1-xO2 to Mn3O4 supported on the rutile (R) phase of TiO2. The above change occurs in the first few hours of reaction and the Mn3O4 on R-TiO2 phase is the active phase of the catalyst and responsible for sustainable activity for Longer duration.

Enhanced light harvesting and charge separation over wormhole mesoporous TiO2-X nanocrystallites towards efficient hydrogen generation - Negi, Sanjay Singh (Sustainable Energy & Fuels, 2019)
Here meso-TiO2-X materials with combined visible light absorption, high surface area, an anatase-rutile heterojunction, and electrically interconnected nanocrystallites in a wormhole mesoporous framework are achieved. Meso-TiO2-X materials were prepared by solution combustion synthesis (SCS), followed by hydrogenation at higher temperatures. The materials are thoroughly characterised by various physicochemical techniques. A small band gap (2.8 eV), type IV-H-2 mesoporosity with a biphasic heterojunction, and small pore depths (10 nm) in a wormhole mesoporous framework are observed with 35AP. Photocatalytic water splitting for hydrogen production and photocurrent generation were carried out with meso-TiO2-X materials under simulated sunlight. A six-fold increase in activity under AM 1.5G irradiation was observed, which is attributed to the generated mid-gap states which lead to band gap reduction, improved optical absorption in the visible and infrared light region resulting in higher charge carrier density. The presence of a biphasic heterojunction between the (1 0 1) anatase and (1 1 0) rutile facets assists in effective charge separation. A low charge diffusional constraint associated with wormhole mesoporosity helps in facile charge transport to the surface for improved charge utilisation in redox reactions.

Facile, sustainable and unassisted plain water oxidation on Au/Ce0.9Ti0.1O2 nanorods in direct sunlight - Dubey, Anjani; Mishra, Abhaya Kumar; Negi, Sanjay Singh; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2022)
Impressive rate of solar water oxidation to molecular oxygen (O-2) has been demonstrated on nanorods (NRs) of Ce0.9Ti0.1O2 (CT-NR) and Au-deposited CT-NR (Au-CT-NR) photocatalysts with a sacrificial agent (Fe3+) and in plain water in one sun condition, direct sunlight and with lambda >= 455 nm. Probably the highest 0 2 yield of 11 mmol/h.g was observed with Au-CT-NR thin film in plain water in direct sunlight, with no sacrificial agent or applied potential. Photoelectrochemical measurements demonstrate a marked reduction in oxidation onset potential of Au-CT-NR by 150 mV with stable photocurrent (0.75 mA/cm(2)), compared to CT-NR (0.23 mA/cm(2)), indicating the operative of plasmon-induced resonant energy transfer (PIRET) process. Effective electron quenching by nanogold and hence low recombination in the depletion region is a critical step for the observation of a high rate of oxygen evolution. In addition to this, a predominant change in the nature of the valence band from O-2p dominated on CeO2 to Ce-4f dominated with CT-NR (due to Ti4+ introduction in CeO2), the efficient light absorption of photocatalysts in thin-film form, functional and effective PIRET process, and facile E-F alignment, enhances the oxygen evolution with Au-CT-NR in direct sunlight and make it highly sustainable. A possible mechanism of water oxidation is proposed from the observed experimental findings.
Keywords: ceria; Electronic integration; Photocatalysis; thin film; water splitting

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment